Finding Glenoid Surface on Scapula in 3D Medical Images for Shoulder Joint Implant Operation Planning-3D OCR - Sadeghi, Majid Mohammad; Kececi, Emin Faruk; Bilsel, Kerem; BİLSEL, İSMAIL KEREM; Aralasmak, AYŞE; ARALAŞMAK, AYŞE (My University, 2017)
Medical imaging has great importance in earlier detection, better treatment and follow-up of diseases. 3D Medical image analysis with CT Scan and MRI images has also been used to aid surgeries by enabling patient specific implant fabrication, where having a precise three dimensional model of associated body parts is essential. In this paper, a 3D image processing methodology for finding the plane on which the glenoid surface has a maximum surface area is proposed. Finding this surface is the first step in designing patient specific shoulder joint implant.
Keywords: Sadeghi M. M. , Kececi E. F. , Bilsel K., Aralasmak A., -Finding Glenoid Surface on Scapula in 3D Medical Images for Shoulder Joint Implant Operation Planning-3D OCR-, 9th International Conference on Machine Vision (ICMV), Nice, Fransa, 18 - 20 November 2016, cilt.10341